Emerging Antimicrobial Drug Resistance in Africa and Latin America: Search for Reasons - Hoellein L; Kaale E; Hebron Mwalwisi Y; Schulze MH; Vetye-Maler C; Holzgrabe U (Dove Medical Press, 2022)
Ludwig Hoellein,1 Eliangiringa Kaale,2 Yonah Hebron Mwalwisi,3 Marco H Schulze,4 Carina Vetye-Maler,5 Ulrike Holzgrabe1 1Institute for Pharmacy and Food Chemistry, Julius-Maximilians-Universität Würzburg, Würzburg, Germany; 2Muhimbili University of Health and Allied Sciences, School of Pharmacy, Dar es Salaam, Tanzania; 3Tanzania Medicines & Medical Devices Authority, Dar es Salaam, Tanzania; 4Georg-August-Universität Göttingen, Institut für Krankenhaushygiene und Infektiologie, Göttingen, Germany; 5Apotheker ohne Grenzen Deutschland e.V., München, GermanyCorrespondence: Ulrike Holzgrabe, Institute for Pharmacy and Food Chemistry, Julius-Maximilians-Universität Würzburg, Am Hubland, Würzburg, 97074, Germany, Tel +49 931 31 85460, Email ulrike.holzgrabe@uni-wuerzburg.deAbstract: Medicine quality and methods for its assessment play a major role in the effectiveness of therapies and the treatment of many infectious diseases. However, poor-quality and/or falsified products are circulating in huge amounts in many low- and middle-income countries and are one of the major reasons why more and more resistant bacteria emerge. The development of resistance is additionally triggered by a plethora of antibiotic medicines which is easily available through pharmacies and unofficial sources. The uncontrolled overuse of these products is a huge problem not only in single countries but worldwide. In this review, we aim to demonstrate the factors which are involved in an emerging resistance development and how strong regulatory authorities, routine quality control by means of proficiency testing, and post-marketing surveillance as well as training personnel and patients can be combined to curb the problem.Keywords: medicine quality, falsified, antimicrobial resistance, proficiency testing, post-marketing surveillance, Africa, Latin America